2023
DOI: 10.1038/s41366-023-01310-8
|View full text |Cite
|
Sign up to set email alerts
|

Likelihood of obesity in early and late childhood based on growth trajectory during infancy

Abstract: Background Childhood obesity rates have reached epidemic levels with Mediterranean countries reporting among the highest numbers globally. Evidence suggests early life factors, including infant growth rate, increase the likelihood of obesity later in childhood. However, optimal rates of infant growth associated with lower odds of future obesity still remain undetermined. The study aim was to determine the optimal infant growth rate associated with a lower likelihood of childhood overweight and ob… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
0
2
0
2
Order By: Relevance
“…In a recently published article, the association between infancy growth rates and overweight/obesity in greek pre-school children (2 – 5 years old) and adolescents (10 – 12 years old) were analyzed. The authors demonstrated a positive association between rapid weight gain during infancy and overweight/obesity at pre-school years and adolescence, with statistical significance in the latter (4). In this study, infancy was defined as the first 6 months of life, which roughly corresponds to the suckling period in our mouse model.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In a recently published article, the association between infancy growth rates and overweight/obesity in greek pre-school children (2 – 5 years old) and adolescents (10 – 12 years old) were analyzed. The authors demonstrated a positive association between rapid weight gain during infancy and overweight/obesity at pre-school years and adolescence, with statistical significance in the latter (4). In this study, infancy was defined as the first 6 months of life, which roughly corresponds to the suckling period in our mouse model.…”
Section: Discussionmentioning
confidence: 98%
“…Alongside high birth weight, another significant risk factor is rapid body weight gain during early life stages (3). Recent studies have shown that accelerated body weight gain within the first six months of life correlates positively with overweight or obesity in pre-school years (age 2-5) and pre-adolescence (age 10-12) (4).…”
Section: Introductionmentioning
confidence: 99%
“…No obstante, esta relación es importante porque el crecimiento en los primeros 6 meses de vida tiene un mayor impacto para determinar el riesgo de sobrepeso y obesidad en el futuro, en comparación con otros periodos de crecimiento. 2 Por lo tanto, la concentración de betaína en la leche materna puede estar influyendo en una etapa crucial para prevenir el riesgo de sobrepeso y obesidad.…”
Section: Característicasunclassified
“…1 Este problema podría iniciar con el crecimiento acelerado durante la lactancia, que es predictor del desarrollo de sobrepeso y obesidad a futuro. 2 Se reconoce al amamantamiento como medio de prevención del crecimiento acelerado en los primeros meses de vida. No obstante, se dan algunos casos de niños amamantados en exclusiva, con crecimiento acelerado y sobrepeso.…”
Section: Introductionunclassified